2000
DOI: 10.1023/a:1009612610389
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper investigates the reaction of stock prices to enactment of the Private Securities Litigation Reform Act of 1995 (PSLRA). Based on a sample of 489 high-technology firms, we find that the PSLRA was wealth-increasing, on average, and that the market reaction is more positive for firms at greatest risk of being sued in a securities class action. However, we also show that the PSLRA was less beneficial for firms likely to be the subject of a meritorious lawsuit. Collectively, our evidence implies that sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In 1995, Congress passed the PSLRA to curtail abusive litigation that hindered firm managers' ability to communicate forecasts to the public market (Johnson, Kasznik, and Nelson 2000). The PSLRA offers public companies Safe Harbor from liability for forward-looking statements.…”
Section: Safe Harbor For Forward-looking Statementsmentioning
confidence: 99%
“…In 1995, Congress passed the PSLRA to curtail abusive litigation that hindered firm managers' ability to communicate forecasts to the public market (Johnson, Kasznik, and Nelson 2000). The PSLRA offers public companies Safe Harbor from liability for forward-looking statements.…”
Section: Safe Harbor For Forward-looking Statementsmentioning
confidence: 99%
“…and testing only for the marginal effects of ESG controversies and ESG performance. We considered extensive previous research that has already examined a large set of potentially relevant explanatory variables for litigation risk(Kim and Skinner 2012;Johnson, Kasznik, and Nelson 2000;Brown, Hillegeist, and Lo 2005;Rogers and Stocken 2005).Johnson et al, Brown et al, and Rogers and Stocken found strong evidence that market and return variables play a vital role in explaining litigation risk-beyond the FPS industry variable fromFrancis et al (1994).…”
mentioning
confidence: 99%